Performance Evaluation of Green Supply Chain Management in Canned Fish (Sardines) Production Unit: A Case of Indonesia - Suryaningrat, Ida Bagus Bagus; Kuswardhani, Nita; Darmaningrum, Sindy Rosa; Purnomo, Bambang Hery; Wibowo, Yuli (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Indonesia's fishing industry, especially in East Java Province, shows great potential but also harms the environment. CV. Pasific Harvest Surabaya (CV. PHB) is a fish canning industry in Banyuwangi Regency, which is currently facing problems such as the supply of raw materials, which continues to decline; the company has not measured and planned the total consumption of energy, fuel, water and the problem of workers who have not received environmental training. Although a waste processing system is in place, the production process still carries the risk of environmental pollution. The researchers collected data through observation, interviews, literature studies, and paired comparison questionnaires. The results of the research reveal that CV. PHB manages three supply chain flows with four supply chain actors. The final performance score is 81.77, with 24 verified KPIs. The KPIs that need performance improvement are packaging time until the product is picked up by the delivery service (D4), time for handling customer complaints (R3), and environmental training for workers (E1).